AERIFY-1/2: two phase 3, randomised, controlled trials of itepekimab in former smokers with moderate-to-severe COPD - Klaus F. Rabe; Fernando J. Martinez; Surya P. Bhatt; Tomotaka Kawayama; Borja G. Cosio; Robert M. Mroz; Maarten M. Boomsma; Helene Goulaouic; Michael C. Nivens; Michel Djandji; Xavier Soler; Ying Liu; et al. (ERJ Open Research)
Background Accumulating data implicate interleukin (IL)-33, a proinflammatory cytokine released locally upon epithelial cell damage, in the pathogenesis of COPD. In a phase 2 study, itepekimab, a human monoclonal antibody against IL-33, reduced exacerbations and improved lung function in a subgroup analysis of former smokers with COPD with an acceptable safety profile. Methods The study designs of AERIFY-1 and AERIFY-2 are described in this article. Discussion The primary objective of AERIFY-1/2 (NCT04701983/NCT04751487), two phase 3 randomised, double-blind, placebo-controlled trials, is to assess the efficacy and safety of itepekimab versus placebo in a population of former smokers with moderate-to-severe COPD over up to 52 weeks. An additional secondary population of current smokers are being enrolled in AERIFY-2. These two studies will enrol patients (aged 40–85 years) with COPD and chronic bronchitis who had ≥2 moderate or ≥ 1 severe exacerbations within the previous year despite standard-of-care triple or double background therapy. All participants are required to have ≥10-pack-year smoking history, and ≥6 months since smoking cessation for former smokers. The primary end-point is the annualised rate of moderate or severe acute exacerbation of COPD. Secondary end-points include change from baseline in pre- and post-bronchodilator forced expiratory volume in 1 s, and annualised frequency of severe exacerbations. Symptomatic end-points include Evaluating Respiratory Symptoms in COPD and St. George's Respiratory Questionnaire, safety and anti-drug antibody responses.